2019
DOI: 10.1101/544395
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Group B Streptococcal surface antigen I/II protein, BspC, interacts with host vimentin to promote adherence to brain endothelium and inflammation during the pathogenesis of meningitis

Abstract: Streptococcus agalactiae (Group B Streptococcus, GBS) normally colonizes healthy adults but can cause invasive disease, such as meningitis, in the newborn. To gain access to the central nervous system, GBS must interact with and penetrate brain or meningeal blood vessels; however, the exact mechanisms are still being elucidated. Here, we investigate the contribution of BspC, an antigen I/II family adhesin, to the pathogenesis of GBS meningitis. Disruption of the bspC gene reduced GBS adherence to human cerebra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…21 Notably, a strong expression of Vim in endothelial cells may favor transendothelial migration. 22 Vim+ aneuploid CECs significantly increased after NCT. High expression of Vim in endothelial cells may increase the probability of transendothelial migration of primary tumor cells and of their conversion to CTCs.…”
Section: Discussionmentioning
confidence: 90%
“…21 Notably, a strong expression of Vim in endothelial cells may favor transendothelial migration. 22 Vim+ aneuploid CECs significantly increased after NCT. High expression of Vim in endothelial cells may increase the probability of transendothelial migration of primary tumor cells and of their conversion to CTCs.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, the structural organization of extracellular vimentin and/or the concurrent PTMs could potentially influence its actions. Based on epitope recognition by a variety of antibodies, it has been reported that the tail domain is accessible in activated platelets [ 45 ] and on the surface of human cerebral microvascular endothelial cells [ 58 ]. Nevertheless, evidence from deletion analysis indicated that the head domain of vimentin could be involved in protein–protein interactions in the extracellular medium [ 44 ].…”
Section: Extracellular Vimentinmentioning
confidence: 99%
“…During acute bacterial meningitis, neutrophils predominate in the cerebral spinal fluid, which is often used as a diagnostic marker. Following interaction with human cerebral microvascular endothelial cells (hCMEC) in vitro, GBS induces a characteristic neutrophilic inflammatory response, including expression of chemoattractants interleukin-8 (IL-8), C-X-C motif chemokine ligand 1 (CXCL-1), and CXCL-2 (33)(34)(35). Similar results are observed in animal models of experimental GBS meningitis, as brain tissue of GBS infected mice shows increased neutrophil and monocyte infiltration compared to naïve controls (35) indicating a close interaction between GBS and granulocytic cells during active infection.…”
Section: Introductionmentioning
confidence: 99%
“…Following interaction with human cerebral microvascular endothelial cells (hCMEC) in vitro, GBS induces a characteristic neutrophilic inflammatory response, including expression of chemoattractants interleukin-8 (IL-8), C-X-C motif chemokine ligand 1 (CXCL-1), and CXCL-2 (33)(34)(35). Similar results are observed in animal models of experimental GBS meningitis, as brain tissue of GBS infected mice shows increased neutrophil and monocyte infiltration compared to naïve controls (35) indicating a close interaction between GBS and granulocytic cells during active infection. Additional studies have shown that, in response to GBS, neutrophils elaborate extracellular traps decorated with lactoferrin (36) and that S100A9, a calprotectin subunit, is present in the blood and amniotic fluid during intrauterine GBS infection (37).…”
Section: Introductionmentioning
confidence: 99%